Treatment of polycarbonate by dielectric barrier discharge (DBD) at atmospheric pressure - Kostov, K. G. [UNESP]; Hamia, Y. A. A. [UNESP]; Mota, R. P. [UNESP]; Santos, A. L. R. dos [UNESP]; Nascente, P. A. P.; IOP (Iop Publishing Ltd, 2014)
Generally most plastic materials are intrinsically hydrophobic, low surface energy materials, and thus do not adhere well to other substances. Surface treatment of polymers by discharge plasmas is of great and increasing industrial application because it can uniformly modify the surface of sample without changing the material bulk properties and is environmentally friendly. The plasma processes that can be conducted under ambient pressure and temperature conditions have attracted special attention because of their easy implementation in industrial processing. Present work deals with surface modification of polycarbonate (PC) by a dielectric barrier discharge (DBD) at atmospheric pressure. The treatment was performed in a parallel plate reactor driven by a 60Hz power supply. The DBD plasmas at atmospheric pressure were generated in air and nitrogen. Material characterization was carried out by contact angle measurements, and X-ray photoelectron spectroscopy (XPS). The surface energy of the polymer surface was calculated from contact angle data by Owens-Wendt method using distilled water and diiodomethane as test liquids. The plasma-induced chemical modifications are associated with incorporation of polar oxygen and nitrogen containing groups on the polymer surface. Due to these surface modifications the DBD-treated polymers become more hydrophilic. Aging behavior of the treated samples revealed that the polymer surfaces were prone to hydrophobic recovery although they did not completely recover their original wetting properties.